2018
DOI: 10.1186/s12917-018-1742-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, crystallization and preliminary X-ray diffraction analysis of swine leukocyte antigen 2 complexed with a CTL epitope AS64 derived from Asia1 serotype of foot-and-mouth disease virus

Abstract: BackgroundCurrently, the structural characteristics of the swine major histocompatibility complex (MHC) class I molecule, also named swine leukocyte antigen class I (SLA-I) molecule need to be further clarified.ResultsA complex of SLA-I constituted by an SLA-2*HB01 molecule with swine β2-microglobulin and a cytotoxic T lymphocyte (CTL) epitope FMDV-AS64 (ALLRSATYY) derived from VP1 protein (residues 64–72) of Asia 1 serotype of foot-and-mouth disease virus (FMDV) was expressed, refolded, purified and crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Currently, FMD vaccine studies using an inactivated vaccine, modified virus inactivated vaccine (DIVA vaccine) [ 24 ], viral vector vaccine [ 25 ], adenovirus [ 26 , 27 , 28 ], virus-like particle (VLP) vaccine (bacterial) [ 29 ], baculovirus [ 30 , 31 ], plant-produced empty capsids [ 32 , 33 ], peptide vaccine (Poly(I:C)) [ 34 ], CpG [ 35 ], plant based recombinant vaccine (alfalfa [ 36 ], chloroplast of tobacco [ 37 ]), RNA vaccine [ 38 ], DNA vaccine (cDNA [ 39 , 40 ], electroporation [ 41 ], T cell [ 42 , 43 , 44 ], B cell [ 45 , 46 ] epitope, APC targeting [ 47 ]), live attenuated vaccine [ 48 , 49 , 50 , 51 ], and antiviral agent [ 52 , 53 ] are underway. However, no high-quality FMD vaccines that surpass the efficacy of the inactivated vaccine have been successfully developed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, FMD vaccine studies using an inactivated vaccine, modified virus inactivated vaccine (DIVA vaccine) [ 24 ], viral vector vaccine [ 25 ], adenovirus [ 26 , 27 , 28 ], virus-like particle (VLP) vaccine (bacterial) [ 29 ], baculovirus [ 30 , 31 ], plant-produced empty capsids [ 32 , 33 ], peptide vaccine (Poly(I:C)) [ 34 ], CpG [ 35 ], plant based recombinant vaccine (alfalfa [ 36 ], chloroplast of tobacco [ 37 ]), RNA vaccine [ 38 ], DNA vaccine (cDNA [ 39 , 40 ], electroporation [ 41 ], T cell [ 42 , 43 , 44 ], B cell [ 45 , 46 ] epitope, APC targeting [ 47 ]), live attenuated vaccine [ 48 , 49 , 50 , 51 ], and antiviral agent [ 52 , 53 ] are underway. However, no high-quality FMD vaccines that surpass the efficacy of the inactivated vaccine have been successfully developed to date.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation, refolding, and crystallization of SLA-2*HB01 and sβ 2 m proteins complexed with peptides were performed as previously reported [ 35 , 39 ]. In this research, additional peptides (shown in Table 1 ) were used in refolding and crystallization with SLA-2*HB01 and sβ 2 m proteins.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, additional peptides (shown in Table 1 ) were used in refolding and crystallization with SLA-2*HB01 and sβ 2 m proteins. Two peptides, Hu64, which is derived from the O serotype of FMDV Tibet/CHA/99 (HuBHK99), and As64, from 1/Jiangsu/China/2005, were crystallized with SLA-2*HB01 and sβ 2 m, and their crystal data were collected as previously reported [ 35 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, CTL epitope characterization has been mostly addressed by in silico predictions and inbred mice, with the understanding that such models need to be confirmed experimentally. For example, Barfoed et al reported a murine H2-Kd-restricted CTL epitope that induced cell immunity in mice but did not achieve a protective effect in other animals [ 104 ]; in contrast, Gao et al described several 9-residue peptides from FMDV VP1 that not only induced CTL response in mice but also provided protective response in guinea pigs [ 105 , 106 , 107 ].…”
Section: Fmdv Antigenic Structurementioning
confidence: 99%